In the shadow of the shtetl : small-town Jewish life in Soviet Ukraine - Veidlinger, Jeffrey, 1971- (Indiana University Press, 2013)
The story of how the Holocaust decimated Jewish life in the shtetls of Eastern Europe is well known. Still, thousands of Jews in these small towns survived the war and returned afterward to rebuild their communities. The recollections of some 400 returnees in Ukraine provide the basis for this book's reappraisal of the traditional narrative of 20th-century Jewish history. These elderly Yiddish speakers relate their memories of Jewish life in the prewar shtetl, their stories of survival during the Holocaust, and their experiences living as Jews under Communism.